The effect of ruminative thought style and workplace ostracism on turnover intention of hotel employees: the mediating effect of organizational identification - Turkoglu,Nuray (2019)
The primary aim of this paper is to reveal the effects of the ruminative thought style and workplace ostracism on hotel employees turnover intention. In addition, the effect of the ruminative thought style and workplace ostracism on hotel employees turnover intention through the mediator role of organizational identification was investigated in this study. The data were collected by convenience sampling between 1 June and 1 October 2018 from the employees of the twelve 5-star hotel businesses in Bodrum, Turkey, yielding 432 valid survey forms. The results showed that ruminative thought style and workplace ostracism increase the turnover intention of hotel employees while organizational identification decreases it. In addition, organizational identification plays a mediating role between a ruminative thought style and turnover intention. Thus, we recommend to the managers that they should create a good working environment, support and participate in social activities with their team, make their employees feel that they are a part of the organization and always state that they value their team.